2010
DOI: 10.1523/jneurosci.2393-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cortical Automaticity in Rule-Based Categorization

Abstract: There is evidence that rule-based category learning is supported by a broad neural network that includes the prefrontal cortex, the anterior cingulate cortex, the head of the caudate nucleus, and medial temporal lobe structures. Although thousands of studies have examined rule-based category learning, only a few have studied the development of automaticity in rule-based tasks. Categorizing by a newly learned rule makes heavy demands on declarative memory, but after thousands of repetitions rule-based categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 33 publications
10
85
1
Order By: Relevance
“…Both the right IFGpo and striatum are commonly identified in rule-based categorization tasks (Aron, Robbins, & Poldrak, 2004; Ashby, Paul & Maddox, 2011; Helie, Roeder, & Ashby, 2010). The contribution of ventral striatum (VS) to correct categorization could be because of our design choice to award points for correct responses: several studies have reported NAcc activity related to anticipation of financial gains or rewards (Knutson, Fong, Bennett, Adams & Hommer, 2003; Knutson & Wimmer, 2007; O'Doherty, et al 2004; Wächter, Lungu, Liu, Willingham & Ashe, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both the right IFGpo and striatum are commonly identified in rule-based categorization tasks (Aron, Robbins, & Poldrak, 2004; Ashby, Paul & Maddox, 2011; Helie, Roeder, & Ashby, 2010). The contribution of ventral striatum (VS) to correct categorization could be because of our design choice to award points for correct responses: several studies have reported NAcc activity related to anticipation of financial gains or rewards (Knutson, Fong, Bennett, Adams & Hommer, 2003; Knutson & Wimmer, 2007; O'Doherty, et al 2004; Wächter, Lungu, Liu, Willingham & Ashe, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The lateral PFC may also support generalization of learned information to unseen category members, a key function of categorization (Pan, Sawa, Tsuda, Tsukada, & Sakagami, 2008). In humans, rule-based categorization engages the caudate during early learning, then the ventrolateral PFC, and finally premotor cortex (Hélie, Roeder, & Ashby, 2011; Soto, Waldschmidt, Hélie, & Ashby, 2013). Computational modeling suggests that, with experience, the PFC can self-organize connections to stimulus and task representations that support rule-based categorization and generalization (Rougier & O'Reilly, 2002; Rougier, Noelle, Braver, Cohen, & O'Reilly, 2005).…”
Section: Mfh and Learningmentioning
confidence: 99%
“…More complex rules are constructed from one-dimensional rules via Boolean algebra (e.g., to produce logical conjunctions, disjunctions, etc.). The neural structures that have been implicated in this process include the prefrontal cortex, anterior cingulate, head of the caudate nucleus, and hippocampus (Ashby et al, 1998; Ashby, Ell, Valentin, & Casale, 2005; Hélie, Roeder, & Ashby, 2010). The computational implementation of the COVIS hypothesis-testing system is a hybrid neural network that includes both symbolic and connectionist components.…”
Section: A Computational Implementation Of Covismentioning
confidence: 99%